New Eocene primate from Myanmar shares dental characters with African Eocene crown anthropoids - Jean-Jacques Jaeger (Nature Portfolio, 2019)
Recent fossil findings have suggested that anthropoid primates originated in Asia before dispersing into Africa. Here, Jaeger and colleagues describe a new fossil Asian primate, Aseanpithecus myanmarensis, that they interpret as a closer relative of African crown anthropoids.